Functional bracing in a femur non-union following fracture related infection: a case report - Khalid, Nazirul Mubin; Sulong, Ahmad Fadzli; Mohd Yusof, Nazri (Malaysian Orthopaedic Association, 2024)
Non-union refers to a disruption in the process of fracture repair, which can be identified through sequential clinical and radiographic assessments. The distinction between septic and aseptic non-union is essential because the treatment strategies are fundamentally different. Non-unions are most often treated surgically as it helps to provide both mechanical stability and good biological environment to promote bone healing. However, there is also the option of managing it conservatively by proper immobilisation using functional brace which is an alternative for surgical procedures and widely reported in tibia non-union cases. To date, there has been no reported case of femur non-union successfully treated with a functional brace. This case report details the success of treatment using a functional brace in a mentally disabled gentleman who sustained a femur non-union following a fracture related infection.